A randomised trial of a medium-chain TAG diet as treatment for dogs with idiopathic epilepsy. Issue 9 (4th September 2015) - Law, Tsz Hong; Davies, Emma S. S.; Pan, Yuanlong; Zanghi, Brian; Want, Elizabeth; Volk, Holger A.
Abstract: Despite appropriate antiepileptic drug treatment, approximately one-third of humans and dogs with epilepsy continue experiencing seizures, emphasising the importance for new treatment strategies to improve the quality of life of people or dogs with epilepsy. A 6-month prospective, randomised, double-blinded, placebo-controlled cross-over dietary trial was designed to compare a ketogenic medium-chain TAG diet (MCTD) with a standardised placebo diet in chronically antiepileptic drug-treated dogs with idiopathic epilepsy. Dogs were fed either MCTD or placebo diet for 3 months followed by a subsequent respective switch of diet for a further 3 months. Seizure frequency, clinical and laboratory data were collected and evaluated for twenty-one dogs completing the study. Seizure frequency was significantly lower when dogs were fed the MCTD (2·31/month, 0–9·89/month) in comparison with the placebo diet (2·67/month, 0·33–22·92/month, P =0·020); three dogs achieved seizure freedom, seven additional dogs had ≥50 % reduction in seizure frequency, five had an overall <50 % reduction in seizures (38·87 %, 35·68–43·27 %) and six showed no response. Seizure day frequency were also significantly lower when dogs were fed the MCTD (1·63/month, 0–7·58/month) in comparison with the placebo diet (1·69/month, 0·33–13·82/month, P =0·022). Consumption of the MCTD also resulted in significant elevation of blood β -hydroxybutyrate concentrations in comparison with placebo diet (0·041 (sd 0·004) v. 0·031 (sd 0·016) mmol/l, P =0·028). There were no significant changes in serum concentrations of glucose ( P =0·903), phenobarbital ( P =0·422), potassium bromide ( P =0·404) and weight ( P =0·300) between diet groups. In conclusion, the data show antiepileptic properties associated with ketogenic diets and provide evidence for the efficacy of the MCTD used in this study as a therapeutic option for epilepsy treatment.